2018
DOI: 10.1016/j.fertnstert.2017.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Ulipristal acetate decreases transforming growth factor β3 serum and tumor tissue concentrations in patients with uterine fibroids

Abstract: Reduction of serum and tissue TGF-β3 concentrations in UFs may be an important component of the effect of UPA on UF biology. Further research in this area is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
2
16
0
1
Order By: Relevance
“…In their study, TGF-β3 was inhibited by increased concentrations of vitamin D [ 98 ]. Their results further confirmed our belief that research about the role of vitamin D in the UF biology is the right direction because TGF-β is considered to be one of the most relevant factors in the pathogenesis of fibrosis-associated diseases [ 46 ], while TGF-β3 is one of the most important TGF-β isoforms in UF biology [ 99 , 100 , 101 ]. Its increased serum levels constitute a risk factor for UF incidence [ 6 ].…”
Section: Discussionsupporting
confidence: 65%
“…In their study, TGF-β3 was inhibited by increased concentrations of vitamin D [ 98 ]. Their results further confirmed our belief that research about the role of vitamin D in the UF biology is the right direction because TGF-β is considered to be one of the most relevant factors in the pathogenesis of fibrosis-associated diseases [ 46 ], while TGF-β3 is one of the most important TGF-β isoforms in UF biology [ 99 , 100 , 101 ]. Its increased serum levels constitute a risk factor for UF incidence [ 6 ].…”
Section: Discussionsupporting
confidence: 65%
“…These observations are also supported by some of the effects of ulipristal acetate (UPA) on UF tumors [133]. Despite the fact that UPA has a potent effect on one of the major UF pathophysiological pathways—progesterone and is TGF-β dependent [27], it also increases the activity of alkaline phosphatase, upregulates caspases, and downregulates TNF-α expression [134]. According to Ciarmela et al, UPA was also found to inhibit the expression and functions of activin A and activin receptor in UF tumor cells [135].…”
Section: Discussionmentioning
confidence: 91%
“…According to the available sources, elevated levels of TGF-β play an important role in UF growth and clinical symptom progression [7,26,27,29,103], which appears to be one of the key factors in myofibroblast transformation and fibrosis progression [17,29,35,37]. Activin A is yet another factor, by no means less important, which was found to be involved in cell proliferation, differentiation, death signaling, and metabolism [81,104].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations